Measuring household interest-rate sensitivity in Denmark - Stine Ludvig Bech; Jakob Guldbæk Mikkelsen (Danmarks Nationalbank, 2021)
In this paper, we evaluate Danish homeowners' interest-rate sensitivity in terms of the partial effect of a 1 percentage point increase in interest rates on homeowners cash flows and balance sheets. We construct two measures to quantify the effect of an increase in interest rates on homeowners. The effect on homeowners' cash flow is measured as the change in the debt service-to-income ratio, i.e. the change in interest and amortisation in per cent of income. The effect on balance sheets is measured as the change in the debt-to-assets ratio, where we model the change in the two primary elements of homeowners' balance sheets: mortgage debt and housing wealth. Overall, the interest-rate sensitivity is limited. Cash-flow sensitivity fell during the 2009- 19 period, coinciding with the fall in the aggregate share of outstanding adjustable-rate mortgages, and the fall in outstanding bank loans. The median and upper tails of the distribution of balance-sheet sensitivity fell as well. However, for a non-negligible share of homeowners, an increase in interest rates will have a substantial effect on their cash flows and balance sheets.
Keywords: D14; G21; E21; 330; Financial stability; household balance sheets; housing finance